Cypermethrin induction of DNA damage and oxidative stress in zebrafish gill cells - Paravani, Enrique Valentin (2019)
Cypermethrin (CYP) is a synthetic pyrethroid insecticide, used to control pests in domestic, industrial and agricultural environments. According to recent reports, it is one of the most common contaminants in freshwater aquatic systems. The aim of this study was to evaluate its potential genotoxic effect and the activation of the superoxide dismutase (SOD) and catalase (CAT) systems of adult zebrafish gill cells after in vivo exposure. The comet assay (CA) demonstrated that gill cells are sensitive to DNA damage after in vitro exposure to hydrogen peroxide (H 2 O 2 ), showing a dose-dependent response. We also found an increase in DNA damage of gill cells following a dose- and time-dependent treatment with CYP. Moreover, it was verified that SOD and CAT activities significantly increased after exposure to 0.6 µg/L CYP, both during six and nine days. The same treatment caused a significant up-regulation of the mRNA levels of Mn-sod and cat genes. These data indicate that CYP causes gill cell´s DNA damage and oxidative stress, modifying the activities of the enzymes responsible for maintaining ROS balance, as well as in their corresponding gene expression levels.